0339 Occupation and risk of prostate cancer in a national population-based cohort study: the canadian census health and environment cohort. (21st August 2017) - Sritharan, Jeavana; MacLeod, Jill; Harris, Shelley; Cole, Donald; Harris, Anne; Tjepkema, Michael; Peters, Paul; Demers, Paul
Abstract : Prostate cancer is one of the most commonly diagnosed cancers in men and further evidence is needed on preventable risk factors. This study investigated the relationship between prostate cancer risk and occupation using a large Canadian cohort. The Canadian Census Health and Environment Cohort was established by linking the 1991 Canadian Census Cohort to the Canadian Cancer Database (1969–2010), Canadian Mortality Database (1991–2011) and the Tax Summary Files (1981–2011). A total of 37 695 prostate cancer cases were identified based on age at diagnosis. Cox proportional hazards models were used to estimate hazards ratios (HR) and 95% confidence intervals (CI). Overall, age standardised prostate cancer rates were observed to be highest in white collar workers and lowest in construction/transportation workers. In men aged 50–74 years, elevated risks were observed in agriculture management (HR=1.11, 95% CI 1.06–1.17), farm work (HR=1.12, 95% CI 1.02–1.23), firefighting (HR=1.16, 95% CI 1.00–1.35), military (HR=1.14, 95% CI 1.00–1.32), police (HR=1.28, 95% CI 1.14–1.42), senior management (HR=1.09, 95% CI 1.02–1.17), office (HR=1.16, 95% CI 1.08–1.24), and finance (HR=1.08, 95% CI 1.03–1.13). Similar findings were observed in men aged 25–49 years, with additional elevated risks in office management (HR=1.19, 95% CI 1.11–1.27) and education (HR=1.05, 95% CI 1.00–1.11). Decreased risks were observed in construction and transportation occupations in both age groups. Findings across agriculture and protective services were consistent with previous studies. Some findings, particularly among management occupations, may be due to screening. Further investigation is needed on job-specific exposures with better understanding on differences in rates across occupations.